Nivel de satisfacción de los pacientes atendidos en las unidades de atención odontológica de la Carrera de Odontología de la UNL en el periodo abril-septiembre 2019 - Aguilar Campoverde, Anggie Verónica (2021)
The UNL career in dentistry plays an important role in promoting oral health in Zone 7 of the country, having as actors who contribute to the professional training of its students users of all age groups who receive a service to promote the health as well as rehabilitation and healing of the stomatognathic system. The specific objectives that are intended to be achieved with this research are: to determine the level of satisfaction of the care provided by the student, to determine the satisfaction level of the accessibility to the DCUs and finally to determine the level of satisfaction regarding the care environment. The current study is qualitative, quantitative and analytical type, cross-sectional and retrospective. The research universe consisted of 1,118 patients and the sample of 286 of them. The results obtained show that 49.73% of the surveyed patients are very satisfied with the clinical care, 53.58% are very satisfied with the accessibility and 51.20% of the surveyed patients are very satisfied with respect to the care environment. In conclusion, the patients are satisfied with the care received in the Dental Care Units of the UNL Dentistry Career. Keywords: Quality Care; Quality of Health Services; Quality, Access and Evaluation of Health Care.